Pengungkapan Corporate Social Responsibility dan Penghindaran Pajak dengan Profitabilitas sebagai Variabel Moderasi - Artini, Ni Made; Setiawan, Putu Ery (E-Jurnal Akuntansi, 2021)
This study aims to obtain empirical evidence regarding the effect of Corporate Social Responsibility (CSR) on tax avoidance with profitability as a moderating variable. This research was conducted at mining sector companies listed on the Indonesia Stock Exchange (BEI) for the 2017-2019 period. The number of observations of 75 samples obtained through nonprobability sampling method with purposive sampling technique. Data collection was carried out by non-participant observation method. The data analysis technique used is Moderated Regression Analysis (MRA). The results showed that CSR disclosure had a negative effect on tax avoidance. Profitability as a moderating variable is able to moderate the effect of CSR disclosure on tax avoidance. Keywords: Corporate Social Responsibility; Profitability; Tax Avoidance.